2020
DOI: 10.3390/atmos11010059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ozone and Clouds on Temporal Variability of Surface UV Radiation and UV Resources over Northern Eurasia Derived from Measurements and Modeling

Abstract: Temporal variability in erythemal radiation over Northern Eurasia (40°–80° N, 10° W–180° E) due to total ozone column (X) and cloudiness was assessed by using retrievals from ERA-Interim reanalysis, TOMS/OMI satellite measurements, and INM-RSHU chemistry–climate model (CCM) for the 1979–2015 period. For clear-sky conditions during spring and summer, consistent trends in erythemal daily doses (Eery) up to +3%/decade, attributed to decreases in X, were calculated from the three datasets. Model experiments sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Trends in UV radiation were calculated from UV measurements for several European stations (Reading (51° N), Uccle (51° N), Thessaloniki (41° N), and Sodankylä (67° N)) [ 60 ]; Northern Eurasia (a region north of 40° N extending from Scandinavia to Siberia) [ 61 ]; and a site near the equator (Quito, Ecuador, 2,850 m above sea level) [ 62 ]. These new studies generally confirmed the conclusions from our last update assessment [ 1 ], i.e., changes in UV radiation during the last 20 years have been small (generally less than ca .…”
Section: Stratospheric Ozone Uv Radiation and Climate Interactionsmentioning
confidence: 99%
“…Trends in UV radiation were calculated from UV measurements for several European stations (Reading (51° N), Uccle (51° N), Thessaloniki (41° N), and Sodankylä (67° N)) [ 60 ]; Northern Eurasia (a region north of 40° N extending from Scandinavia to Siberia) [ 61 ]; and a site near the equator (Quito, Ecuador, 2,850 m above sea level) [ 62 ]. These new studies generally confirmed the conclusions from our last update assessment [ 1 ], i.e., changes in UV radiation during the last 20 years have been small (generally less than ca .…”
Section: Stratospheric Ozone Uv Radiation and Climate Interactionsmentioning
confidence: 99%
“…Trends in erythemal daily doses (D ery ) were calculated for the period 1979–2015 over Northern Eurasia (a region between 40° and 80° N and extending in longitude from Scandinavia to Siberia) using simulations by a climate chemistry model (INM-RSHU 34 ), re-analyses of atmospheric data (ERA-Interim 35 ), and data from satellite measurements (TOMS/OMI) [ 242 ]. For cloud-free conditions, statistically significant increases in D ery of up to 3% per decade were found for spring and summer over large areas and attributed to decreases in TCO.…”
Section: Variability In Uv Radiation and Trends From Observationsmentioning
confidence: 99%
“…This finding would be useful to constrain solar forcing magnitude if some reconstructions of the ozone are available. Chubarova et al [9] analyzed the evolution of erythemal radiation over Northern Eurasia caused by total column ozone and cloud amount variabilities, acquired from the observations and model simulations. They found generally positive trends for all months and locations except in the central Arctic in July, which is driven by the increase in cloud amount.…”
Section: Stratospheric Ozone Evolutionmentioning
confidence: 99%